Smart And Green Campus Regulatory Design As Untirta's Legal Policy To Improve the Quality of Participatory Higher Education - Agus Prihartono P.S.; Lia Riesta Dewi; Fatkhul Muin (Faculty of Law, Universitas Pekalongan, 2023)
The formation of a policy regulation does not have general guidelines because it is the authority of each institution which is not binding on other institutions and is weak in giving sanctions, while the formation of a statutory regulation must be guided by Law Number 12 of 2011 concerning the Establishment Laws and regulations that have been amended by Law Number 15 of 2019 by providing space for the public to participate. This research uses qualitative research methods with a normative juridical approach. Sultan Ageng Tirtayasa University is one of the State campuses in Banten, which needs to design smart and green campus regulations to improve the quality of participatory higher education. This policy is a legal policy to shape the quality of higher education as smart and green campuses